EFFECT OF RATIO OF SURFACE AREA ON THE CORROSION RATE - Dody Prayitno; M. Irsyad (Universitas Mercu Buana, 2018)
Aluminum and steel are used to be a construction for a building outdoor panel. Aluminum and steel are connected by bolt and nut. An atmosphere due to a corrosion of the aluminum. The corrosion possibly to cause the hole diameter of bolt and nut to become larger. Thus the bolt and nut can not enough strong to hold the panel. The panel may collapse. The aim of the research is first to answer a question where does the corrosion starts. The second is to know the effect of ratio surface area of steel with aluminum on the corrosion rate of aluminum. The research is started to cut a steel and aluminum flat into variation surface areas. Next, the steel and aluminum are bolted as samples for corrosion test. The samples are divided into two groups. The group A was immersed in NaCl (10%) and the groups B was immersed in HCl 10%. The corrosion rate is calculated with loss weight method. The conclusions are as follow. The corrosion does not start from the bolt hole but from the edge of aluminum. Increasing the ratio of surface area (steel/aluminum) increases the corrosion rate of aluminum.